2015
DOI: 10.1080/17461391.2015.1106590
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental intervention on sedentary time, musculoskeletal comfort and work ability in office workers

Abstract: Sit-stand workstations offer a potential strategy to reduce prolonged occupational sitting. This controlled intervention study examined the effects of an environmental intervention on occupational sedentary time, musculoskeletal comfort and work ability, and the usability of sit-stand workstations in office work via a self-reported questionnaire. The intervention group (n = 24) used sit-stand workstations during the 6-month intervention period, and the control group (n = 21) used traditional sitting workstatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 39 publications
0
37
1
5
Order By: Relevance
“…Out of 26 studies in total, 12 reported a significant reduction in workplace sitting . Among the remaining studies, nine reported sitting reductions, but the effects were not statistically significant ; in which two out of the nine reported borderline significant reductions .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Out of 26 studies in total, 12 reported a significant reduction in workplace sitting . Among the remaining studies, nine reported sitting reductions, but the effects were not statistically significant ; in which two out of the nine reported borderline significant reductions .…”
Section: Resultsmentioning
confidence: 98%
“…The results of quality assessment are summarized in Table . Two studies were rated to be of ‘high quality’ , 10 of ‘good’ and 14 of ‘fair’ methodological quality . Main factors that affected the methodological quality included inadequate descriptions of group allocation, incomparable groups at baseline, final analysis not adjusted for baseline sedentary behaviour and outcome assessment not independent and blinded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, two recent studies highlighted the benefits of environmental interventions designed to reduce sitting for subjectively assessed lower back pain (Foley, Engelen, Gale, Bauman, & Mackey, 2016), and neck and shoulder discomfort (Gao, Nevala, Cronin, & Finni, 2016). However, there is a need for further research to provide more robust evidence to support office worker's anecdotal beliefs about the acute and chronic musculoskeletal benefits of reduced sitting.…”
Section: Discussionmentioning
confidence: 99%